2023
DOI: 10.1038/s41564-022-01275-w
|View full text |Cite
|
Sign up to set email alerts
|

Metavirome of 31 tick species provides a compendium of 1,801 RNA virus genomes

Abstract: The increasing prevalence and expanding distribution of tick-borne viruses globally have raised health concerns, but the full repertoire of the tick virome has not been assessed. We sequenced the meta-transcriptomes of 31 different tick species in the Ixodidae and Argasidae families from across mainland China, and identified 724 RNA viruses with distinctive virome compositions among genera. A total of 1,801 assembled and complete or nearly complete viral genomes revealed an extensive diversity of genome archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 59 publications
4
32
1
Order By: Relevance
“…While our findings indicate that phylogenetic distance among mosquitos constrained virus transmission, there are cases of generalist viruses that can infect multiple mosquito species. Hence, counter to earlier ideas, virome compositions are not completely distinct among insect species 7,10,12 . Notably, our results also imply that the host specificity of mosquito-associated viruses exists on a spectrum rather than adhering to a rigid “generalist-specialist” dichotomy 28,33 .…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…While our findings indicate that phylogenetic distance among mosquitos constrained virus transmission, there are cases of generalist viruses that can infect multiple mosquito species. Hence, counter to earlier ideas, virome compositions are not completely distinct among insect species 7,10,12 . Notably, our results also imply that the host specificity of mosquito-associated viruses exists on a spectrum rather than adhering to a rigid “generalist-specialist” dichotomy 28,33 .…”
Section: Discussioncontrasting
confidence: 82%
“…Some viruses appear to be predominantly associated with particular mosquito species, although sporadic host switching events are frequent, such as the case of Mosquito narna-like virus SC1. This phenomenon of frequent host switching has also been observed in rabies viruses of bats 34 , and in recent metagenomics studies in mammals 6 and ticks 7 . The frequent spillover events, along with the frequent co-infection of viruses within individual mosquitos, are likely to contribute to increased genetic diversity among viruses circulating in mosquito communities.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For instance, some newly discovered tick‐associated viruses (such as the viruses identified in Zhang et al., 2021 and Kong et al., 2022) were not included in the data set. Furthermore, a recent examination of tick metaviromes showed that approximately 70% of the 223 viruses identified in their study had never been previously documented in ticks (Ni et al., 2023). Hence, it is important to acknowledge that some putative novel tick‐associated viruses may have been missed due to the absence of similar viruses for comparison.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, a recent examination of tick metaviromes showed that approximately 70% of the 223 viruses identified in their study had never been previously documented in ticks (Ni et al, 2023).…”
Section: (A) (B)mentioning
confidence: 91%